(3TQM hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3eMehO Hf YHjOGddg Hf EHQGgje GdeMHhHjj GdMfaj , HQgGf GdTQjYI,J (B673 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI s
(3BNQgG (B:s
(3aGdMeO ddg GdPi habfi GJeGeg eTJedkG Ydi CcKQ eSGFd GdgOGjI hGdUdGI hGdSdGe GdCJeGf GdCcedGf Ydi fHjg eMeO hBdg CLeYjf s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3hbGjI GdgOGjI GfXQ cTa GdXfhf L(B2 (3U` (B2020 s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs